An experimental approach to thermochemical conversion of a fuel particle in a fluidized bed. (15th October 2018) - Salmasi, A.; Shams, M.; Chernoray, V.
Highlights: Chemical Conversion and hydrodynamics of fuel particle is studied simultaneously. The effect of bed temperature is investigated on the devolatilization rate. Pyrolysis time of particle is measured at different ranges of fluidization velocity. Mass loss of the fuel particle is recorded due to the devolatilization. Abstract: Measuring the temperature of a fuel particle during the thermochemical process inside the fluidized bed is of great importance in order to obtain detailed knowledge of the conversion behavior of the fuel particle and so optimize the combustion performance. In this study a number of experiments were done in order to register the temperature and hydrodynamics of a biomass fuel particle in a fluidized bed during the devolatilization process of a biomass particle. The experiments were done in a 2D fluidized bed with a front transparent window in order to use the particle image velocimetry (PIV) method to obtain information on the hydrodynamics of the fuel particle and inert bed material inside the bed. A thermocouple was also used to measure the temperature of the particle during the conversion. Experiments were done at a fluidized bed temperature and fluidization velocity in the range of 350–450 °C and 0.2–0.6 m/s, respectively. The effect of the bed's temperature and fluidization velocity on the drying and devolatilization process of the biomass fuel particle was investigated. The results indicate that the bed's temperature and fluidization velocity have a significant effect on the mass and heat transfer between the fuel particle and the bed during the conversion process.